PROVISION OF VITAMIN C AND VITAMIN D FOOD INGREDIENTS AGAINST THE REDUCTION OF BLOOD GLUCOSE LEVELS IN DIABETES MELLITUS TYPE II INDICATED RESPONDENTS: Diabetes Mellitus Tipe II; Vitamin C; Vitamin D - rizki_nk Rizki Nurmalya; Farah Nuriannisa; Anugrah Linda Mutiarani; Kartika Yuliani (Journal of Health Community Service, 2021)
This community service was carried out to improve the knowledge of Kutisari residents who identified had diabetes mellitus. The preliminary study was conducted regarding residents who identified with diabetes mellitus with deficiency of vitamin C and vitamin D intake. This community service program lasts for one year. The activity in this community service was collecting the data of respondents with diabetes mellitus, gave nutrition counselling, and directly provided food sources of vitamin C and vitamin D. Besides provided leaflets of vitamin C and vitamin D food sources, the nutrition counselling also measured the respondent’s blood sugar levels. Checking blood glucose levels was carried out to determine the glucose levels of residents who were identified as having diabetes mellitus. Intake of food sources of vitamin C and vitamin D was expected to lower blood glucose levels. The respondent received guava and chicken eggs as the food source of vitamin C and vitamin D. The purpose of this community service is to improve the respondent's knowledge about the food sources of vitamin C and vitamin D. Those foods will reduce the high blood glucose levels close to the normal values. The output of this community service activity is an online-published report.